Controle de posição com restrição à orientação de um Veículo Aéreo Não-Tripulado tipo Quadrirrotor - Silva, Andre Tavares da (2014)
Quadrotors aircraft are composed by four propellers mounted on four engines on a cross or x disposition, and, in this structure, the engines on the same arm spin in the same direction and the other arm in the opposite direction. By rotating each helix generates vertical upward thrust. The control is done by varying the rotational speed of each motor. Among the advantages of this type of vehicle can cite the mechanical simplicity of construction, the high degree of maneuverability and the ability to have vertical takeoffs and landings. The modeling and control of quadrirrotores have been a challenge due to problems such as nonlinearity and coupling between variables. Several strategies have been developed to control this type of vehicle, from the classical control to modern. There are air surveillance applications where a camera is fixed on the vehicle to point forward, where it is desired that the quadrotor moves at a fixed altitude toward the target also pointing forward, which imposes an artificial constraint motion, because it is not desired that it moves laterally, but only forwards or backwards and around its axes . This restriction is similar to the naturally existing on robots powered by wheels with differential drive, which also can not move laterally, due to the friction of the wheels. Therefore, a position control strategy similar to that used in this type of robot could be adapted for aerial robots like quadrotor. This dissertation presents and discusses some strategies for the control of position and orientation of quadrotors found in the literature and proposes a strategy based on dynamic control of mobile robots with differential drive, called the variable reference control. The validity of the proposed strategy is demonstrated through computer simulations